Downregulation of the α1- and β1-subunit of sGC in Arterial Smooth Muscle Cells of OPSCC Is HPV-Independent. (October 2018) - Korkmaz, Y.; Roggendorf, H.C.; Siefer, O.G.; Seehawer, J.; Imhof, T.; Plomann, M.; Bloch, W.; Friebe, A.; Huebbers, C.U.
The nitric oxide (NO)–sensitive soluble guanylyl cyclase (sGC) is a heterodimeric enzyme with an α and β subunit. NO binds to heme of the β1 -subunit of sGC, activates the enzyme in the reduced heme iron state in vascular smooth muscle cells (VSMCs), and generates cGMP-inducing vasodilatation and suppression of VSMC proliferation. In the complex tumor milieu with higher levels of reactive oxygen species (ROS), sGC heme iron may become oxidized and insensitive to NO. To change sGC from an NO-insensitive to NO-sensitive state or NO-independent manner, protein expression of sGC in VSMC is required. Whether sGCα1 β1 exists at the protein level in arterial VSMCs of oropharyngeal squamous cell carcinoma (OPSCC) is unknown. In addition, whether differences in the genetic profile between human papillomavirus (HPV)–positive and HPV-negative OPSCC contributes to the regulation of sGCα1 β1 is unclear. Therefore, we compared the effects of HPV-positive and HPV-negative OPSCC on the expression of sGCα1 β1 in arterial VSMCs from tumor-free and tumor-containing regions of human tissue sections using quantitative immunohistochemistry. In comparison to the tumor-free region, we found a decrease in expression of both α1 - and β1 -subunits in the arterial VSMC layer of the tumor-containing areas. The OPSCC-induced significant downregulation of the α1 - and β1 -subunits of sGC in arterial VSMC was HPV-independent. We conclude that the response of sGC to NO in tumor arterial VSMCs may be impaired by oxidation of the heme of the β1 -subunit, and thus, α1 - and β1 -subunits of sGC could be targeted to degradation under oxidative stress in OPSCC in an HPV-independent manner. The degradation of sGCα1 β1 in VSMCs may result in increased proliferation of VSMCs, promoting tumor arteriogenesis in OPSCC. This can be interrupted by preserving the active heterodimer sGCα1 β1 in arterial VSMCs.